Politics, intellectuals, and faith : essays - Feldman, Matthew (Ibidem Press, 2020)
This wide-ranging collection of academic essays examines the various undertakings by modern intellectuals and ideologues in the process of propaganda and political debate. Matthew Feldman calls attention to the substantial role played in post-Great War Europe and the US by religions'both familiar monotheisms like Christianity and secular 'political faiths''over the last century of upheaval and revolutionary change. While the first part considers Ezra Pound as a case study in fascist 'conversion' in Mussolini's Italy, leading to extensive propaganda, the second half examines other fascist ideologues like Martin Heidegger to fascist murderer Anders Behring Breivik, before turning to other leading ideologies in modern Europe and the US, communism and liberalism, covering key figures from Thomas Merton and Albert Camus to the Russian Constructionists and Samuel Beckett, with especial focus on the subjects of modern warfare, political terrorism, and genocide, ranging from Stalinist gulags to the war in Iraq. With thought-provoking discussion of the interplay between belief and modern politics as understood by familiar intellectual voices, this volume will be of interest to scholars and general readers alike.
Keywords: Philosophy -- Political aspects.; Philosophie -- Aspect politique.; PHILOSOPHY / Religious.; Philosophy